2021
DOI: 10.3390/ijms22136862
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Metabolic Syndrome Research and Therapeutics

Abstract: Metabolic syndrome (MetS) is a well-defined yet difficult-to-manage disease entity. Both the precipitous rise in its incidence due to contemporary lifestyles and the growing heterogeneity among affected populations present unprecedented challenges. Moreover, the predisposed risk for developing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in populations with MetS, and the viral impacts on host metabolic parameters, underscores the need to investigate this mechanism thoroughly. Recent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…The metabolic syndrome that may include insulin resistance, NAFLD, chronic low-level inflammation, as well as other serious co-morbidities [ 1 ]. Precipitated mainly by obesity, the metabolic syndrome may eventually lead to type 2 diabetes (T2D) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic syndrome that may include insulin resistance, NAFLD, chronic low-level inflammation, as well as other serious co-morbidities [ 1 ]. Precipitated mainly by obesity, the metabolic syndrome may eventually lead to type 2 diabetes (T2D) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome remains the most common non-communicable disease that is characterized by central obesity, insulin resistance, hyperlipidaemia, and hypertension ( Bishehsari et al, 2020 ). MetS increases the risk of developing several chronic diseases, including T2DM, NAFLD, cardiovascular diseases, and cancer ( Chen et al, 2021b ; Kao and Huang, 2021 ). The contributors of MetS include genetic factors, and lifestyle, such as dietary over-consumption of HFD ( Wutthi-In et al, 2020 ).…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Clinically, the impacts of inflammatory status induced by gut dysbiosis have been displayed in a wide spectrum of cardiovascular disease. Our previous review summarised the correlation between gut microbiota and inflammation in patients with metabolic syndrome [ 68 ]. Luedde et al observed a significantly lower diversity index in 20 individuals with heart failure secondary to ischaemic or dilated cardiomyopathy, which was marked by the depletion of Coriobacteriaceae , Erysipelotrichaceae , and Ruminococcaceae [ 69 ].…”
Section: The Role Of Gut Microbiotamentioning
confidence: 99%